2020
DOI: 10.1111/ppc.12447
|View full text |Cite
|
Sign up to set email alerts
|

Is health literacy associated with mental health literacy? Findings from Mental Health Literacy Scale

Abstract: Purpose: This study aims to measure associated factors of Mental Health Literacy (MHL) among Minnesotans by using the Mental Health Literacy Scale and Andersen's Health Behavior Model. Design and methods: This study utilized cross-sectional survey data with 732 participants.Findings: Participants in higher education groups showed higher MHL levels than those who have less education. Non-Latino Whites had higher MHL levels than any other racial group. Participants who engaged in social groups had higher MHL lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 55 publications
4
15
0
2
Order By: Relevance
“…This relationship between MHL and HL needs to be carefully treated, however, as the questionnaire did mainly focus on general HL and did not include a comprehensive conceptualization of MHL, but a rather limited number of MHL-associated items. Nonetheless, the present findings are in accordance with another study that also showed a substantial association between MHL and HL ( 22 ). In addition to the present approach, the referred study considered HL as a predictor of MHL.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This relationship between MHL and HL needs to be carefully treated, however, as the questionnaire did mainly focus on general HL and did not include a comprehensive conceptualization of MHL, but a rather limited number of MHL-associated items. Nonetheless, the present findings are in accordance with another study that also showed a substantial association between MHL and HL ( 22 ). In addition to the present approach, the referred study considered HL as a predictor of MHL.…”
Section: Discussionsupporting
confidence: 94%
“…While many studies examined the relationship of HL and sociodemographic factors (16,17), health behavior (16)(17)(18)(19), and health outcome (16,17,20), so far only few studies examined these aspects in relation to MHL. These studies related MHLaspects to sociodemographic characteristics such as age (21)(22)(23), gender (21)(22)(23)(24), education (21)(22)(23), financial situation (23,25), and rural residence (24,26). Studies investigating MHL-aspects in the context of health behavior showed that stigma could be associated with more frequent alcohol and drug abuse (27), and low rates of help-seeking could be associated with higher rates of substance use disorders (28).…”
Section: Introductionmentioning
confidence: 99%
“…All examinations converged in that higher levels of these factors were associated with higher levels of HL. Some of these factors were study time [ 32 ], ,last cervical cancer pap test within 36 months [ 70 ], being member of a social organization [ 26 ], engaging in social groups [ 27 ], better information/access to books [ 60 ], adherence to Mediterranean diet [ 47 ], use of specific medical websites [ 33 ] and being a member of health club/welfare group in their community within last 6 months [ 52 ] (see Additional file 1 for summary of all study findings).…”
Section: Resultsmentioning
confidence: 99%
“…Individuals who themselves have a mental illness or know someone who has one are in a better position to manage the disease-related process (easily understanding health information, fulfilling medical procedures and instructions, easily accessing health services, etc.) (Lee et al, 2019). It is expected that this situation will improve mental health literacy.…”
Section: Variables Affecting Mental Health Literacy In Adultsmentioning
confidence: 99%
“…MHL is an important determinant of the potential to enhance the mental health of individuals, families, and societies (Benuto et al, 2019; Lee et al, 2019). It is of great importance to determine the level of MHL to understand the variables related to mental health literacy (age, gender, stigmatization, help‐seeking, etc.…”
Section: Introductionmentioning
confidence: 99%